2019
DOI: 10.1016/j.tcr.2019.100202
|View full text |Cite
|
Sign up to set email alerts
|

Globe rupture caused by a camel bite

Abstract: Camel bites are uncommon. They are more common during the rutting season where male camels become more aggressive. Herein, we report a unique case of a 25-year-old man who was repeatedly bitten to his face and neck by an aggressive camel that resulted in left eye evisceration, parotid duct, and facial nerve injury. To our knowledge, Globe rupture caused by a camel bite has not been previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
(15 reference statements)
0
6
1
Order By: Relevance
“…Balac et al reported the only case of a ruptured globe in the literature that caused by a camel bit that end-up by evisceration. 8 Unlike the previous report, the globe was preserved in our case and ended up with light-perception vision. Both cases show that a CRI with ruptured globe might lead to deleterious visual outcomes.…”
Section: Discussioncontrasting
confidence: 86%
“…Balac et al reported the only case of a ruptured globe in the literature that caused by a camel bit that end-up by evisceration. 8 Unlike the previous report, the globe was preserved in our case and ended up with light-perception vision. Both cases show that a CRI with ruptured globe might lead to deleterious visual outcomes.…”
Section: Discussioncontrasting
confidence: 86%
“…Using its sharply pointed canine teeth and strong long jaw, the victim can be efficiently gripped, lifted, and shaken with a jerky movement. Deep body structures can be severely injured despite the superficial appearance of the wound 7,10 . Two patients were kicked by a camel to their jaw resulting in mandibular fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Given the camel's size, force, and unpredicted behavior, injuries caused by camels can be life-threatening. The mechanism of camel-related injuries varies and includes kicks, falls, bites, and collisions with vehicles 7,8 . The CF area sustains more frequent and severe injuries including soft tissue lacerations, facial bone fractures, skull fractures, intracranial hemorrhages, and brain injuries [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Camels are domestic animals commonly seen in Asia, Africa, and Arabian countries and are an important source of milk, food, transport, and racing competitions. 54 Camels are considered quiet and obedient animals, but male camels become irritable, highly unpredictable, and aggressive in the rutting season from December till March. The people close to camels and their caregivers are more vulnerable to camel related injuries (CRI).…”
Section: Camel Related Ocular Injuriesmentioning
confidence: 99%
“…58 However, Bolack K et al reported a case of camel bite resulting in severe oculofacial injury where a patient had extensive corneal laceration with the expulsion of intraocular content. 54 They were not able to salvage the globe, and thus evisceration was performed.…”
Section: Camel Related Ocular Injuriesmentioning
confidence: 99%